Soft governance in education: The PISA study and the Bologna Process in Switzerland - Tonia Bieber (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
This paper analyzes the importance of governance of international organizations (IOs) to Swiss policy making in the field of education. The focus is on the Bologna Process driven by the European Commission, and the 'Programme for International Student Assessment' (PISA) of the Organization for Economic Cooperation and Development (OECD). The theoretical framework draws on sociological institutionalism and rationalism. The results demonstrate that IOs gave impulses for domestic reforms by applying diverse governance instruments. National transformation capacities of veto-players and cultural guiding principles on education in Switzerland were not able to hinder these impulses as supposed. Instead, the empirical findings show a surprisingly high impact of IO governance instruments, particularly of standard setting, coordinative activities and discursive dissemination on reforms in Swiss education policy-making. This is because IO governance modified domestic guiding principles on education so that they matched those of the IOs. Another reason is that the domestic level strategically used the international initiatives of PISA and Bologna to overcome long-standing backlog of reform. – – Dieses Arbeitspapier untersucht die Bedeutung von Governance internationaler Organisationen (IOs) für die Schweizer Politikgestaltung im Bildungsbereich. Der Fokus liegt dabei auf dem Bologna Prozess, der von der Europäischen Kommission vorangetrieben wird, und der PISA-Studie (Programme for International Student Assessment) der OECD (Organization for Economic Cooperation and Development). Der theoretische Rahmen beruht auf dem soziologischen Institutionalismus und Rationalismus. Die Resultate zeigen, dass IOs durch Anwendung diverser Governance-Instrumente wichtige Impulse für innerstaatliche Reformen gaben. Nationale Transformationskapazitäten - Vetospieler und kulturelle Leitideen der Bildung - der Schweiz verhinderten dies nicht. Statt dessen demonstrieren die empirischen Befunde einen unerwartet hohen Einfluss von IO Governance-Instrumenten - insbesondere von Standard Setting, koordinativen Aktivitäten und diskursiver Verbreitung - auf die Schweizer Gestaltung von Bildungspolitik. Dies lag daran, dass IO Governance innerstaatliche Leitideen der Bildung so modifizierte, dass sie denen der IOs entsprachen. Zudem nutzten nationale Akteure die internationalen Initiativen von PISA und Bologna strategisch, um lange anhaltenden Reformstau zu überwinden.
Keywords: 300; Bologna Process; Direct Democracy; Education Policy-Making; EU; Federalism; International Initiative; International Organization; OECD; PISA Study; Switzerland; Veto-Player; Bildungspolitik; International; Governance-Ansatz; Hochschulreform; Bildungsniveau; Schweiz